Analisis Keamanan Modifikasi Metode Caesar Chiper Dalam Teknik Enkripsi Dan Deskripsi - Rinaldi, Rizky (Fakultas Komputer - Universitas Universal, 2022)
The confidentiality and integrity of a message that will be conveyed is one aspect that every individual expects in carrying out information exchange activities. Many techniques that can be used to secure data include cryptography. Cryptography aims to provide security services (which are also referred to as security aspects). To be able to use cryptographic techniques, a method is needed, one of which is the Caesar Cipher method. Changes made to the character set in the caesar chiper algorithm have succeeded in making this algorithm have a better level of security. The result of the analysis of this study is that the chipertext pattern that is incited is more varied so that the level of security of this method is better than before.